The aetiopathogenesis of capsular contracture: A systematic review of the literature. Issue 3 (March 2018) - Bachour, Yara; Verweij, Stephan P.; Gibbs, Susan; Ket, Johannes C.F.; Ritt, Marco J.P.F.; Niessen, Frank B.; Mullender, Margriet G.
Summary: Background: Capsular contracture is the most frequent complication after breast augmentation or reconstruction with breast implants. The immune system plays a prominent role in capsular contracture formation, albeit to an unknown extent. Bacterial contamination in situ has been hypothesized to be causative for capsular contracture. How this relates to the immunological processes involved is unknown. This article aims to provide an overview of immunological and bacterial factors involved in development of capsular contracture. Materials and methods: We undertook a systematic literature review focused on immunological factors and microbiota in relation to capsular contraction around implants. This systematic review was performed in accordance with the PRISMA guidelines. PubMed, EMBASE, and the Cochrane databases were searched from inception up to October 2016. Included studies were assessed for the following variables: subject characteristics, number of capsules, primary indication for surgery, surgical procedure, follow-up or implant duration, study methods, type of antibiotics or medical therapies and outcomes related to microbiota and immunological factors. Results: Data on immunological factors and bacterial contamination were retrieved from 64 included studies. Notably the presence of macrophages and Staphylococcus epidermidis within capsules was often associated with capsular contracture. Conclusion: This review provides a clear overview of the immunological factors associated with capsular contracture and provides a hypothetical immunological model for development of the disease. Furthermore, an overview of bacterial contamination and associations with capsular contracture has been provided. Follow-up research may result in clinical recommendations to prevent capsular contracture.